(untitled) (Al-Aasar, 2025)
This study, Postcolonial Echoes: Reconstructing Memory, History, and Urban Identity in Rizwan Akhtar’s Lahore: I Am Coming, explores how Akhtar’s poetry engages with the lingering shadows of colonial history while reimagining the city of Lahore as a living archive of memory and identity. Through a postcolonial lens, the paper examines how Akhtar reconstructs fragmented histories of displacement, belonging, and nostalgia, transforming the city into a metaphor for both personal and collective consciousness. Lahore emerges not merely as a geographical space but as a textured narrative, a site where memory intersects with modern urban realities and where the poet’s diasporic voice negotiates themes of home and exile. The study highlights how Akhtar’s poetic language reclaims cultural memory, resists historical erasure, and redefines urban identity in postcolonial Pakistan. By tracing the emotional and spatial dimensions of Lahore, this research argues that Akhtar’s poetry becomes an act of reclamation: a dialogue between past and present, between the self and the city. Ultimately, the paper positions Lahore: I Am Coming as a powerful postcolonial text that revives the city’s historical consciousness while articulating the complex relationship between place, identity, and poetic remembrance.